Trend 1998 - 2009. World Bank. Gender Statistics: General Economic Conditions | Country: Faroe Islands | Socioeconomic Indicator: GDP (current US$), 1998-2009. Data-Planet™ Statistical Ready Reference by Conquest Systems, Inc. Dataset-ID: 051-007-004. - World Bank (Data-Planet™ Statistical Ready Reference by Conquest Systems, Inc., 2015)
World Bank (2015). Gender Statistics: General Economic Conditions | Country: Faroe Islands | Socioeconomic Indicator: GDP (current US$), 1998-2009. Data-Planet™ Statistical Ready Reference by Conquest Systems, Inc. [Data-file]. Dataset-ID: 051-007-004. Dataset: Indicators provide general data on economic development levels, including gross domestic product, gross national income, poverty headcounts, and more, in developing and advanced economies, as available. For definitions of indicators, see the World Bank’s 2013 publication, Little Data Book on Gender 2013, http://hdl.handle.net/10986/13206 The Gender Statistics database provides indicators on key gender topics, including demographics, education, health, labor force, and political participation. Data are provided, as available, from 213 reporting economies. Data sources and years of coverage vary across indicators. Much of the data comes from the statistical systems of World Bank member countries. The quality of the data depends on how well these national systems perform. Errata announcements are posted periodically by the World Bank at http://data.worldbank.org/about/data-updates-errata. Category: Industry, Business, and Commerce, International Relations and Trade Source: World Bank Founded in 1944 as a result of the Bretton Woods Conference, the World Bank is an independent specialized agency of the United Nations that provides financial and technical assistance to developing countries in order to foster economic growth and reduce poverty. Today, the World Bank Group comprises five institutions owned by 187 member countries: the International Bank for Reconstruction and Development (IBRD), which focuses on middle-income and creditworthy poor countries; the International Development Association (IDA), which focuses on least developed countries; the International Finance Corporation (IFC); the Multilateral Guarantee Agency (MIGA); and the International Centre for the Settlement of Investment Disputes (ICSID). http://www.worldbank.org/ Subject: Economic Conditions, Gross Domestic Product (GDP), Gender, Economic Development